2012
DOI: 10.1123/ijspp.7.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Oxygenation in Men and Women During Repeated-Sprint Exercise

Abstract: Purpose:To understand the role of O2 utilization in the sex differences of fatigue during intermittent activity, we compared the cerebral (prefrontal lobe) and muscle (vastus lateralis) oxygenation of men and women during repeated-sprint exercise (RSE).Methods:Ten men and 10 women matched for initial-sprint mechanical work performed ten, 10 s cycle sprints (with 30 s of rest) under normoxic (NM: 21% FIO2) and acute hypoxic (HY: 13% FIO2) conditions in a randomized single-blind and crossover design. Mechanical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
45
4
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 31 publications
6
45
4
6
Order By: Relevance
“…Provided that ∆[tHb] reflects blood perfusion, it is suggested that RS performance is not primarily limited by oxygen delivery to skeletal muscle, as this is indeed supported in the literature [24][25][26][27] , neither by blood flow-related removal of metabolites. Rather, RS performance is considered to be predominantly determined by neuromuscular factors 24-28 , including, but not limited to, neural drive, muscle excitability, PCr stores and recovery rate 28 .…”
Section: Discussionmentioning
confidence: 91%
“…Provided that ∆[tHb] reflects blood perfusion, it is suggested that RS performance is not primarily limited by oxygen delivery to skeletal muscle, as this is indeed supported in the literature [24][25][26][27] , neither by blood flow-related removal of metabolites. Rather, RS performance is considered to be predominantly determined by neuromuscular factors 24-28 , including, but not limited to, neural drive, muscle excitability, PCr stores and recovery rate 28 .…”
Section: Discussionmentioning
confidence: 91%
“…This may relate to reduced cerebral oxygenation, since studies in hypoxia have demonstrated that diminished cerebral oxygen availability is associated with decreased central drive and fatigue. Specifically during RS exercise, decreased cerebral oxygenation was associated with decreased work capacity 38 39…”
Section: Discussionmentioning
confidence: 99%
“…For example, total mechanical work during ten 10 s cycle sprints interspersed with 30 s of rest was reduced (−8%) in hypoxic (FiO 2 0.13, ∼3600 m) versus normoxic conditions 13. In hypoxia, a ∼9-fold to 10-fold increase in deoxygenation of active muscles (assessed via near-infrared spectroscopy) occurs rapidly during the first repetition of a series of sprints 13 39. However, as this deoxygenation quickly plateaus, and is relatively similar in normoxia and hypoxia, the results have been interpreted to mean that the level of muscle deoxygenation per se, and presumably muscle O 2 extraction, is unlikely to limit CAC 13 39.…”
Section: Exercising and Competing At Altitudementioning
confidence: 99%
“…In hypoxia, a ∼9-fold to 10-fold increase in deoxygenation of active muscles (assessed via near-infrared spectroscopy) occurs rapidly during the first repetition of a series of sprints 13 39. However, as this deoxygenation quickly plateaus, and is relatively similar in normoxia and hypoxia, the results have been interpreted to mean that the level of muscle deoxygenation per se, and presumably muscle O 2 extraction, is unlikely to limit CAC 13 39. On the other hand, the capacity of the muscle to get reoxygenated during recovery periods between efforts has been incriminated in the performance decline in hypoxia 40.…”
Section: Exercising and Competing At Altitudementioning
confidence: 99%